Mise sous silence des actions antidiscriminatoires dans l’accès aux soins. Le champ périnatal face aux discriminations à l’encontre des femmes étrangères en France - Louise Virole (Association Anthropologie Médicale Appliquée au Développement et à la Santé, 2021)
Since the 1990s, French perinatal health policies have identified foreign women as a population with high perinatal risk to be addressed as a priority within dedicated facilities. Although in practice these facilities fight against the discrimination that this population faces in the access to healthcare, their anti-discriminatory dimension is not visible. This article analyzes the mechanisms of invisibility of these anti-discriminatory actions within the field of perinatal care, with regard to the contradictory logics of French health and immigration policies. The silencing of anti-discriminatory action in perinatal health policy texts, in the targeting of dedicated facilities, and in the practices of healthcare professionals hinders foreign women’s awareness of discriminatory processes. Due to this, the women’s ability to mobilize themselves against discrimination is therefore limited.